2020
DOI: 10.3390/biomedicines8060141
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Native Autoantigens in Rheumatoid Arthritis

Abstract: The majority of patients diagnosed with rheumatoid arthritis (RA) have developed autoantibodies against neoepitopes in proteins that have undergone post-translational modification, e.g., citrullination or carbamylation. There is growing evidence of their molecular relevance and their potential utility to improve diagnosis, patient stratification, and prognosis for precision medicine. Autoantibodies reacting to native proteins may also have a role in RA pathogenesis, however, their reactivity patterns remain mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 77 publications
0
24
0
Order By: Relevance
“…RA antibody systems are remarkably diverse, characterized by the presence of those against native proteins as well as those containing posttranslational modi cations (PTMs) [42,43]. While current models of RA have embraced PTMs as core principles of pathogenesis [42,44], α-native protein antibodies are not adequately explained by the PTM-centric paradigm of autoantigen selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA antibody systems are remarkably diverse, characterized by the presence of those against native proteins as well as those containing posttranslational modi cations (PTMs) [42,43]. While current models of RA have embraced PTMs as core principles of pathogenesis [42,44], α-native protein antibodies are not adequately explained by the PTM-centric paradigm of autoantigen selection.…”
Section: Discussionmentioning
confidence: 99%
“…For α-hnRNP-A2/B1 autoantibodies has already been published that it is also associated with less erosive disease, exclusively in early RA [18,29]. Recently, several more reactivities against native proteins in RA have been published [43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Poulsen et al. investigated the global reactivity of autoantibodies in RA patients ( 13 ). Additionally, Horn et al.…”
Section: Proteome Microarraysmentioning
confidence: 99%
“…McAndrew et al applied the IMMUNOME ™ array in autoantibody profiling with SLE serum samples (36, 85). Similarly, Poulsen et al investigated the global reactivity of autoantibodies in RA patients(13).…”
mentioning
confidence: 99%
“…However, the development of autoimmune disorders is not always based on oxidized antigens. Instead, some antigens are native [72], citrullinated [73,74] or deaminated [75]. Interestingly, Hultqvist and colleagues have shown that elevating the low oxidative burst capacity led to suppressing an autoimmune response [76,77].…”
Section: Concept and Challenges Of Multi-ros-modified Autologous Tumor Vaccinesmentioning
confidence: 99%